2018
DOI: 10.1007/s10943-018-0679-y
|View full text |Cite
|
Sign up to set email alerts
|

The Comparison of Death Anxiety, Obsession, and Depression Between Muslim Population with Positive and Negative Religious Coping

Abstract: Death anxiety, obsession, and depression constitute three dimensions of death distress which can be influenced by religious coping in religious individuals. The aim of this study was to compare death anxiety, depression, and obsession between Muslims with positive and negative religious coping. In a cross-sectional study, a sample of 339 participants were selected via stratified random sampling method. The participants were screened using the Brief Religious Coping Scale, in which 60 individuals were identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 27 publications
1
15
0
2
Order By: Relevance
“…Studies have shown that many individuals regard religion as a source of coping with the difficult moments of their lives (Mohammadzadeh and Najafi 2020;Koenig 2012;Willis et al 2019). Death anxiety is often accompanied by the experience of fear, sadness, and anger, and individuals attempt to find a way to cope with them.…”
Section: Religious Coping With Death Anxietymentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that many individuals regard religion as a source of coping with the difficult moments of their lives (Mohammadzadeh and Najafi 2020;Koenig 2012;Willis et al 2019). Death anxiety is often accompanied by the experience of fear, sadness, and anger, and individuals attempt to find a way to cope with them.…”
Section: Religious Coping With Death Anxietymentioning
confidence: 99%
“…Although greater religious participation is not a guaranteed remedy of death anxiety, Alvarado argued that strong religious conviction and belief in an afterlife could reduce death anxiety (Alvarado et al 1995). In fact, religious faith, spiritual belief, and life satisfaction decrease death anxiety and act as a preventive factor against feelings of existential despair (Lewis 2014;Mohammadzadeh and Najafi 2020). A number of studies indicate the role of spiritual experiences and life satisfaction as a coping mechanism (Moore 2013;Saini et al 2016;Taghiabadi et al 2017).…”
Section: Religious Coping With Death Anxietymentioning
confidence: 99%
“…One of correlates of death distress is cultural religious spiritual issues (Jong et al, 2018). For example, some findings found among English sample (Maltby & Day, 2000a), Muslim Lebanese (Abdel‐Khalek, 1998a), Saudi Arabia sample (Almostadi, 2012) and Iranians (Dadfar, Bahrami, Sheybani Noghabi, & Askari, 2016; Dadfar & Lester, 2017a; Mohammadzadeh, 2015; Mohammadzadeh & Najafi, 2010, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Hasil analisis regresi penelitian ini sesuai dengan penelitian dari Mohammadzadeh & Najafi (2018) yang menunjukkan bahwa religiusitas dapat menjadi prediktor bagi kesejahteraan subjektif dimana ketika tingkat religiusitas Islam tinggi, tingkat kesejahteraan subjektif pun tinggi. Kepercayaan dan praktik agama dipercaya dapat mengurangi ketidakberdayaan dan kecemasan pada permasalahan.…”
Section: Gambar Grafik Interaksi Variabel Moderasiunclassified